Synthesis and Evaluation on Anticonvulsant Activities of Pyrazolyl Semicarbazones - Deng*, Xian-Qing; Song, Ming-Xia; Yu, Hai-Hong (Asian Journal of Chemistry, 2014)
In this paper, a series of 2-[(5-phenoxy-3-methyl-1-phenyl-1H-pyrazol-4-yl)-methylene]hydrazine carboxamides were synthesized and evaluated for their anticonvulsant activities using the maximal electroshock method. Their neurotoxicities were determined applying the rotarod test. Interestingly, all compounds showed anticonvulsant activity with long duration of protection effects in the maximal electroshock test. Among which, compound 5m was found to have promising anticonvulsant activity, which gave an ED50 of 42.4 mg/kg and a protective index value of 3.7, possessing better anticonvulsant activity and higher safety than marketed drugs valproate, but weaker than phenobarbital. Furthermore, the antagonistic activity against seizures induced by pentylenetetrazole of the compound 5m was also established, which suggested that compound 5m may exert anticonvulsant activity through g-aminobutyric acid (GABA)-mediated mechanisms.